2009
DOI: 10.1016/j.jcrimjus.2008.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Differences in female and male involvement in lethal violence in Russia

Abstract: Relatively little is known of the distributions of homicide event characteristics in non-Western nations in which women relative to men are involved. This article utilizes unique homicide narratives drawn from Russian court and police records to compare homicide victim, offender, and event characteristics by sex of victim and separately by sex of offender. Results from logistic regression show that homicides in which a female was the victim or offender were more likely to occur between intimates and to occur i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 41 publications
1
21
0
Order By: Relevance
“…This thesis is corroborated by systematic review studies that have shown that when a partner is a heavy alcohol user, women are more likely to become victims of fatal and non-fatal domestic violence 9,11,35 .…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…This thesis is corroborated by systematic review studies that have shown that when a partner is a heavy alcohol user, women are more likely to become victims of fatal and non-fatal domestic violence 9,11,35 .…”
Section: Discussionmentioning
confidence: 76%
“…Another hypothesis is that the younger generation of men, especially in the most socially vulnerable regions, are more exposed to alcohol and drug abuse and, therefore, are more likely to become victims and perpetrators of violence, including gender violence 5,6,11,26 . This thesis is corroborated by systematic review studies that have shown that when a partner is a heavy alcohol user, women are more likely to become victims of fatal and non-fatal domestic violence 9,11,35 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current literature supports the hypothesis that female violent offenders display a different offense pattern in comparison to male violent offenders. Female violent offending is often characterized by the victims of women often being people close to them, the crime a result of interpersonal conflict - this includes parents, husbands and boyfriends, as well as children [ 9 , 10 , 13 , 18 , 20 - 22 ]. In comparison to men, women are more likely to commit a violent crime at home.…”
Section: Introductionmentioning
confidence: 99%
“…Men have born the brunt of intergroup conflict dating back to hunter-gatherer societies (Van Vugt, 2009 ), and behavioral vestiges of this pattern have been consistently shown to persist to modern day. Cross-culturally, male-on-male violence accounts for more than half of homicide crimes (Jason et al, 1983 ; Eckhardt and Pridemore, 2009 ; Häkkänen-Nyholm et al, 2009 ), while the vast majority of homicides that do involve female victims or perpetrators take place between family members or acquaintances (Kellermann and Mercy, 1992 ). Extending to the modern day, males near-exclusively bear the brunt of violence from strangers or outgroup individuals.…”
Section: Discussionmentioning
confidence: 99%